Corona cell RNA sequencing from individual oocytes revealed transcripts and pathways linked to euploid oocyte competence and live birth. Issue 5 (May 2016) - Parks, Jason C.; Patton, Alyssa L.; McCallie, Blair R.; Griffin, Darren K.; Schoolcraft, William B.; Katz-Jaffe, Mandy G.
Abstract: Corona cells surround the oocyte and maintain a close relationship through transzonal processes and gap junctions, and may be used to assess oocyte competence. In this study, the corona cell transcriptome of individual cumulus oocyte complexes (COCs) was investigated. Isolated corona cells were collected from COCs that developed into euploid blastocysts and were transferred in a subsequent frozen embryo transfer. Ten corona cell samples underwent RNA-sequencing to generate unique gene expression profiles. Live birth was compared with negative implantation after the transfer of a euploid blastocyst using bioinformatics and statistical analysis. Individual corona cell samples produced a mean of 21.2 million sequence reads, and 307 differentially expressed transcrpits ( P < 0.05; fold change ≥2). Enriched pathway analysis showed Wnt signalling, mitogen-activated protein kinases signalling, focal adhesion and tricarboxylic acid cycle to be affected by implantation outcome. The Wnt/beta-catenin signalling pathway, including genes APC, AXIN and GSK3B, were independently validated by real-time quantitative reverse transcription. Individual, corona cell transcriptome was successfully generated using RNA-sequencing. Key genes and signalling pathways were identified in association with implantation outcome after the transfer of a euploid blastocyst in a frozen embryo transfer. These data could provide novel biomarkers for the non-invasive assessment of embryo viability.